Effects of Li3+ and Ni9+ Ion Beams on Polyether Sulfone Polymer. Issue 3 (1st August 2013) - Ramola, R. C.; Semwal, Anju; Negi, Ambika; Joshi, Veena; Singh, Fouran
ABSTRACT: High‐energy ion beam irradiation of polymer is an effective technique to enhance the optical, structural, and mechanical properties. So polyether sulfone (PES) films were irradiated by lithium ions (energy 45 MeV, charge state 3+) and nickel ions (energy 120 MeV, charge state 9+) with fluence varying from 3 × 10 10 to 3 × 10 12 ions/cm 2 . Ion‐induced optical, structural, and surface modifications were studied by ultraviolet‐visible (UV–Vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X‐ray diffractrometer (XRD), and atomic force microscopy (AFM). PES suffers degradation under irradiation. It is observed that the band gap of the polymer decreases with ion fluence. The decrease in the band gap was found to be more in the case of the Ni ion beam as compared to the Li ion beam. The intensity of the infrared bands, characteristics of different chemical functional groups are found to be decreased with swift heavy ion (SHI) irradiation. Significant loss of crystallinity was observed at higher fluences. Atomic force microscopy showed that the roughness of the polymer surface increased with increasing fluence © 2013 Wiley Periodicals, Inc. Adv Polym Technol 2013, 32, 21360; View this article online atwileyonlinelibrary.com . DOI 10.1002/adv.21360